If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(98-y)6=12
We move all terms to the left:
(98-y)6-(12)=0
We add all the numbers together, and all the variables
(-1y+98)6-12=0
We multiply parentheses
-6y+588-12=0
We add all the numbers together, and all the variables
-6y+576=0
We move all terms containing y to the left, all other terms to the right
-6y=-576
y=-576/-6
y=+96
| 8‐3x=‐13 | | 5(j-91)=40 | | 3/2x+1/2x=5.5+5/2 | | 55-o=42 | | 4x+5-9x=10 | | 9x+3-7x+25=20 | | 2(6y-7)=70 | | 3/2x+1/2x=5/1/2+5/2 | | x+16=4x+1=3x+9 | | 4x+5-9x=10* | | 3x^{2}+13=-134 | | 6m+24=24+6m | | 5(j−91)=40 | | 8(4w+9)/5=-5 | | 2(3x+12)=6x+24 | | 9y+2y+12=67 | | 3/2x+1/2x=51/2+5/2 | | 12=6(y−98) | | 3x=1/2(54) | | 72=8(z+1) | | 2+1y=y+8 | | 4(r+7)=4+2r | | -4p-8=(-8+5p) | | 3x=1/254 | | 12x-5=5+12x | | 3-8c=43 | | 40=4f+12 | | 10x-4(-2.5)=46 | | 16x-27=5x | | 6y-15+2y+30+11y-44=180 | | 4s+12=-20 | | 5n−18=2 |